Unpacking Government Policy's Impact on EFL Teachers' Lesson Planning - Joko Nurkamto; Kristian Adi Putra (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2025)
Government policies are crucial in shaping English as a Foreign Language (EFL) teachers' lesson planning, often creating conflicts between national mandates and local classroom realities. This study investigates how senior EFL teachers in Surakarta, Central Java, navigate these policy directives while designing lesson plans. The research examines the impact of rigid policy enforcement on teachers' autonomy and adaptability in meeting diverse student needs. Using a biographical narrative inquiry approach, the study captures teachers' lived experiences with policy implementation. Three senior EFL teachers with over a decade of teaching experience participated in the study. Data collection involved document analysis of curriculum guidelines and lesson plans, complemented by in-depth interviews. The data were analyzed using an interactive qualitative analysis model, focusing on data condensation, display, and conclusion verification. Findings indicate that lesson planning is often treated as a bureaucratic obligation rather than an instructional tool due to inconsistent policy guidelines and insufficient institutional support. Teachers struggle with unclear requirements, lack of format uniformity, and minimal feedback, leading them to rely on past lesson plans rather than creating context-specific ones. To enhance lesson planning effectiveness, teachers emphasize the need for standardized exemplars, expert-developed guidelines, and professional training that prioritizes pedagogical impact over policy compliance. The study recommends balancing regulatory mandates with teacher autonomy to make lesson planning more relevant and effective in classroom instruction